The evaluation of ecosystem health based on hybrid TODIM method for Chinese case - Liu, Peide; Rong, Lili; Teng, Fei (Technological and Economic Development of Economy, 2019)
The health evaluation of urban ecosystem is the need of urban sustainable development and the construction of urban ecological civilization, in order to scientifically evaluate the ecosystem health, in this paper, we establish the mathematical model based on hybrid multiple attributes decision-making. Firstly, we introduce the original city ecosystem health evaluation indexes which reflect on Vitality, Composition Structure, Recovery Capacity, The Ecological System Continually Offering Service Function, Population Health and Ecosystem Cognition ecosystem health. Then in order to obtain the reasonable weights, we integrate the subjective weights by linguistic AHP method and objective weights by deviation maximization method, and get the combined weights for city ecosystem health evaluation indexes. Further, according to the characteristics of the different indexes, we propose an extended TODIM method to evaluate the city ecosystem health in which the indexes take the form of real number, interval number, and probabilistic linguistic term set. Moreover, with respect to the evaluation values of city ecosystem health in Jinan from 2011 to 2015, this paper evaluates the health status of Jinan ecological system, and analyzes the role of various indicators in the process of city ecological development. Result shows that: (1) Jinan ecosystem health status remained at the sub-health state from 2011 to 2015, and the ecological situation is not optimistic. (2) Prominent problems restricting are lack of investment in environmental protection efforts, increasing pollutant emissions, and imperfect industrial structure. To solve the problems in the healthy development of Jinan urban ecosystem, this paper puts forward corresponding countermeasures and suggestions to improve the healthy development of urban ecosystem. First published online 17 April 2019